2003
DOI: 10.1074/jbc.c300203200
|View full text |Cite
|
Sign up to set email alerts
|

A Globin in the Nucleus!

Abstract: Cytoglobin and neuroglobin are recently discovered members of the globin family. In situ hybridization localized neuroglobin mainly in brain and retina, while cytoglobin was expressed ubiquitously in all analyzed tissues. In the present study, polyclonal antibodies were raised against both proteins and the distribution of them was studied by immunocytochemistry at tissue and subcellular level. Cytoglobin immunoreactivity was uniformly distributed and found in all tissues studied. At the subcellular level, cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
134
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 147 publications
(149 citation statements)
references
References 48 publications
13
134
2
Order By: Relevance
“…Ngb in the Chloride Cells Suggests Another Association of Ngb with Mitochondria-With the exception of the expression in some endocrine tissues (19,20), Ngb has been assumed to be an exclusively neuronal protein. Here we show by immunofluorescence studies, ISH, and Western blotting that Ngb was also present in the chloride cells of zebrafish gills.…”
Section: Discussionmentioning
confidence: 99%
“…Ngb in the Chloride Cells Suggests Another Association of Ngb with Mitochondria-With the exception of the expression in some endocrine tissues (19,20), Ngb has been assumed to be an exclusively neuronal protein. Here we show by immunofluorescence studies, ISH, and Western blotting that Ngb was also present in the chloride cells of zebrafish gills.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemistry studies showed that cytoglobin is located in the cytoplasm in mouse connective tissues, and nucleus as well as cytoplasm of neurons, implying the respiratory function (Schmidt et al 2004). Moreover, the nuclear location of cytoglobin in mouse neural and endocrine cells was also reported (Geuens et al 2003). When human cytoglobin was expressed in Cos7 cells, the protein in some cells was exclusively localized to the nucleus and in others to the cytoplasm and nucleus (J. Matsubara and S. Taketani, unpublished data), indicating that the localization of cytoglobin changed, dependent on conditions of cells.…”
Section: Contribution Of Iron and Heme To Oxygen-sensing Systemmentioning
confidence: 98%
“…These two hydroxylases are localized in the nucleus and in the cytoplasm, respectively. Interestingly, CYGB has been localized in the nucleus and in the cytoplasm (5,54) and is up-regulated during hypoxia (21).…”
Section: On the Reaction Of 4-pds With Ngb And Human Hbamentioning
confidence: 99%